The Over-education Wage Penalty Among PhD Holders: A European Perspective - François Rycx; Giulia Santosuosso; Guillaume Vermeylen (Global Labor Organization (GLO), 2022)
While the literature on the incidence and wage effects of over-education is substantial, specific results for doctoral graduates are surprisingly scarce. This article aims to fill this gap, not only by measuring the prevalence of over-educated PhD holders in Europe (i.e. in EU Member States and the UK), but also by estimating their wage penalty relative to what they could have earned in a job corresponding to their level of education. Using a unique pan-European dataset, we rely on two alternative measures of over-education and control stepwise for four groups of covariates (i.e. socio-demographic characteristics, skills needed for the job, other job-specific characteristics and motivations for employment) in order to interpret the over-education wage penalty in light of theoretical models. Depending on the specification adopted, we find that over-educated PhD holders face a wage penalty ranging from 25 to 13.5% with respect to their well-matched counterparts. Our results also show that the over-education wage penalty is significantly higher for PhD holders who are both over-educated and over-skilled and especially for those who are both over-educated and dissatisfied with their jobs. Finally, unconditional quantile regressions highlight that the over-education wage penalty among PhD holders increases greatly along the wage distribution.
Keywords: J21; J24; 330; PhD graduates; over-education; over-skilling; job satisfaction; wages; Europe